zbMATH — the first resource for mathematics

More on a rational recurrence relation. (English) Zbl 1069.39024
The paper is mainly concerned with the long-term behavior of the solutions of the difference equation $x_{n+1}=\frac{x_{n-1}}{1+x_{n-1}x_n}, \quad n=0,1,2,\dots \tag{de}$
where the initial conditions $$x_{-1},~x_0$$ are real numbers. An explicit formula of the solution of equation (de) is given by
$x_n=\begin{cases} x_{-1} \frac{\prod_{i=0}^{[(n+1)/2]-1} (2ix_{-1}x_0+1)} {\prod_{i=0}^{[(n+1)/2]-1} ((2i+1)x_{-1}x_0+1)} &\quad\text{if } n\text{ is odd}\\ x_0 {\frac{\prod_{i=1}^{n/2} ((2i-1)x_{-1}x_0+1)} {\prod_{i=1}^{n/2} (2i x_{-1}x_0+1)}} &\quad\text{if } n\text{ is even} \end{cases} \tag{ef}$ Formula (ef) was, first, presented and justified by means of mathematical induction by C. Cinar [Appl. Math. Comput. 158, 809–812 (2004; Zbl 1066.39007)]. However, the author of this note derives the formula in a constructive way by introducing the change of variables $$x_{n+1}x_n=z_n$$. Furthermore, by utilizing formula (ef), he shows that
1) If $$x_{-1}x_0 \neq 0,~ -1/n,~n\in \mathbb{N}$$, then every solution of equation (de) converges to zero.
2) If $$x_{-1}x_0=0$$, then every solution of equation (de) is periodic of period 2.
Finally, as noted by the author, the difference equation
$y_{n+1}=\frac{by_{n-1}}{b+cy_{n-1} y_n},\quad n=0,1,2,$ where $$b$$ and $$c$$ are positive real numbers, can be reduced to equation (de) by introducing the change of variables $$y_n=\sqrt{b/c}x_n$$.

MSC:
 39A20 Multiplicative and other generalized difference equations 39A11 Stability of difference equations (MSC2000)
Zbl 1066.39007
Full Text: